Ethnobotanical contributions to global fishing communities: a review - Jimlea Nadezhda Mendoza; Natalia Hanazaki; Baiba Prūse; Agnese Martini; Maria Viktoria Bittner; Sophia Kochalski; Edison Macusi; Aimee Ciriaco; Giulia Mattalia; Renata Sõukand (BMC, 2023)
Abstract Background Ethnobotanical knowledge about the role of plants in fisheries provides valuable ecological information vital for sustainable management of local resources; however, it is diluted and understudied globally. This literature review aims to map the knowledge of plant use within traditional fishing communities. Methods Through the PRISMA method, we identified and selected 34 articles reporting the use of plants in fisheries, and including 344 taxa of plants and algae. Uses of plants and algae were grouped into different categories. Results In the novel categorization of fishery-related uses we proposed, the most mentioned were for fishing and building/repair of fishing artifacts and habitat-related uses, while the records of plants related to fiber uses, providing aid in fishing management and species causing problems, were among the least mentioned. Semi-structured interview is most commonly used with local resource users, especially fishery experts, in exploring perceptions on plant use within traditional fishing communities. Diversity was high in all the recorded families, but most were reported locally. Conclusion Ethnobotanical studies with fishers are not common in the documented literature but they provide a large number of use reports. On the basis this review, in most of the world, the information is of a casual and sporadic nature. Fishers can provide information on aquatic plants and algae that create problems and aid in fishing management, which are crucial in understanding the ecosystem of a region experiencing environmental challenges. This knowledge is greatly understudied globally and undergoing a rapid decline, as highlighted in several of the reviewed articles. Thus, further systematic research on fishery-related uses of plants by fisherfolk is needed considering its potential contribution to the sustainable management of fishery resources.